MODAL ANALYSIS OF A SATELLITE WITH DIFFERENT MATERIALS - Aguiar, Lucas Rafael Carneiro de; Carneiro, Sergio Henrique da Silva; Paiano, Salvatore (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
For placing an object in any Earth orbit, it is extremely necessary to follow safety rules. The non-use of this can be destroyable for the launching system. Because of that, theÂ launching company Kosmotras® requires that the satellite UniSat7 from GAUSS srl® pursueÂ a high level of structural security. The Kosmotras® requests a modal analysis and that theÂ natural frequencies of the satellite must be higher than 20 Hertz in longitudinal direction andÂ 10 Hertz in lateral. For achieving this results, it is needed to use materials that increase the total stiffness and decrease the mass of the satellite. It was used 3 types of materials to beÂ applied in this study: Aluminium alloy plate, honeycomb composite material made of aluminiumÂ and aluminium honeycomb core with carbon fiber plate sandwich composite. ThroughÂ computational analysis made in ANSYS®, it was proved that the last one material is the mostÂ suitable for aerospace uses. This is explained by the fact that the composite materials (mainlyÂ the honeycomb sandwich panels) have the lowest density and highest stiffness.Â  Keywords: Natural frequencies, Modal analysis, Composite materials, Structural dynamics